Effect of three live covers (Crotalaria juncea L., Pueraria phaseoloides (Roxb.) Benth., and Vigna radiata (L.) R. Wilczek) on the plant-soil interface of a clonal plantation of Tectona grandis L. f. - Carvajal Arroyo, David Antonio (2026)
[Introduction]: The use of live cover crops for weed management is an agroecological strategy that influences the physical, biological, and chemical properties of the soil and is particularly relevant in Latin America, where intensive herbicide use in agricultural and forestry systems generates cumulative impacts on the soil. [Objective]: Evaluate the effect of three coverages on the growth of teak trees, the suppression of weeds, and the chemical composition (macronutrients, micronutrients, organic matter, carbon, nitrogen, and pH) and physical properties of the soil (bulk density, penetrability, and temperature) in a clonal plantation of Tectona grandis L. f. in Pocosol, San Carlos, Costa Rica. [Methodology]: A randomized complete block design with four replications was used. Three cover crop species were established: Crotalaria juncea L. (crotalaria), Pueraria phaseoloides (Roxb.) Benth. (kudzú) y Vigna radiata (L.) R. Wilczek (mung bean). The experiment began in 2021, and in 2024 macro- and micronutrients, penetration resistance, bulk density, soil chromatography, tree growth, and weed cover were evaluated. [Results]: An increase in carbon, organic matter, pH, and calcium saturation was observed, along with a decrease in acidity saturation, phosphorus, and copper. The combination of V. radiata and C. juncea showed the highest values in tree height and diameter. [Conclusions]: P. phaseoloides was the only cover crop species that remained on site, exerting control over weeds; however, it was less efficient in terms of growth, indicating the need for proper management in the early years of planting and the determination of optimal planting density.